IMPLEMENTING AN EMPATHETIC APPROACH AND CREATIVE MEDIA TO IMPROVE STUDENTS' UNDERSTANDING OF EARLY MARRIAGE IN ISLAMIC JUNIOR HIGH SCHOOLS - Rani Ajeng Ayu Safitri; AA Musyaffa (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to examine the implementation of an empathetic approach supported by creative learning media to improve students’ understanding of early marriage in Islamic Religious Education at the Islamic junior high school level. This study employed Classroom Action Research using the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection. The participants were 15 ninth-grade students of Madrasah Tsanawiyah Nurul Huda. Data were collected through learning achievement tests, observation sheets, student response questionnaires, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques across two action cycles. The findings showed that the integration of an empathetic approach and creative learning media improved students’ cognitive understanding, classroom participation, reflective thinking, and empathetic awareness regarding early marriage. Students became more able to identify the educational, psychological, social, and religious consequences of early marriage and demonstrated more critical attitudes toward the issue. The study implies that Islamic Religious Education can function as a contextual and transformative learning space for addressing sensitive social issues. However, the study was limited to one classroom with a small number of participants, so broader studies are needed to strengthen generalizability. This study offers an instructional framework that integrates empathy-based pedagogy and creative media within Islamic Religious Education to promote students’ critical and moral awareness of early marriage.